Azidoimidazolinium Salts: Safe and Efficient Diazo‐transfer Reagents and Unique Azido‐donors. Issue 7 (21st December 2016) - Kitamura, Mitsuru
Abstract: 2‐Azido‐1, 3‐dimethylimidazolinium chloride (ADMC) and its corresponding hexafluorophosphate (ADMP) were found to be efficient diazo‐transfer reagents to various organic compounds. ADMC was prepared by the reaction of 2‐chloro‐1, 3‐dimethylimidazolinium chloride (DMC) and sodium azide. ADMP was isolated as a crystal having good thermal stability and low explosibility. ADMC and ADMP reacted with 1, 3‐dicarbonyl compounds under mild basic conditions to give 2‐diazo‐1, 3‐dicarbonyl compounds in high yields, which were easily isolated in virtue of the high water solubility of the by‐products. ADMP showed high diazo‐transfer ability to primary amines even in the absence of metal salt such as Cu(II). Using this diazotization approach, various alkyl/aryl azides were directly obtained from their corresponding primary amines in high yields. Furthermore, naphthols reacted with ADMC to give the corresponding diazonaphthoquinones in good to high yields. In addition, 2‐azido‐1, 3‐dimethylimidazolinium salts were employed as azide‐transfer and migratory amidation reagents. Abstract : 2‐Azido‐1, 3‐dimethylimidazolinium chloride (ADMC) and its corresponding hexafluorophosphate (ADMP) were found to be efficient diazo‐transfer reagents to various organic compounds. ADMP was isolated as a crystal having thermal stability and low explosibility characteristics. In addition to their diazo‐transfer ability (N2 donor), azidoimidazolinium salts showed unique reactivity for azidation (N3 donor) and migratory amidation.